Themes Focused on Interdisciplinarity and Sustainable Development Worldwide V.1 2023
DOI: 10.56238/tfisdwv1-069
|View full text |Cite
|
Sign up to set email alerts
|

Natural and artificial dyes: its health risks

Abstract: The aim of this study was to research the use of food dyes and their risks to human health. Its methodology was descriptive bibliographic review. Based on the survey, it is verified that although natural dyes are the most indicated, artificial ones are the most used by the food industry because they have high stability, uniformity in the color conferred, high tintorial power, exemption from microbiological contamination and relatively low production cost.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…These risks are generally greater in the case of artificial colorants, which have been introduced to the market often because of their high stability and low economic cost [3]. In this respect, a survey has shown that, although natural colorants are the most suitable, artificial colorants are the most widely used by the food industry, as they have high stability, uniformity in the color imparted to foods, high coloring power, freedom from microbiological contamination and, what's more, relatively low production costs, [4]. However, compared with natural colorants, the use of artificial colorants is limited by the relatively greater risks associated with their consumption [5].…”
Section: Introductionmentioning
confidence: 99%
“…These risks are generally greater in the case of artificial colorants, which have been introduced to the market often because of their high stability and low economic cost [3]. In this respect, a survey has shown that, although natural colorants are the most suitable, artificial colorants are the most widely used by the food industry, as they have high stability, uniformity in the color imparted to foods, high coloring power, freedom from microbiological contamination and, what's more, relatively low production costs, [4]. However, compared with natural colorants, the use of artificial colorants is limited by the relatively greater risks associated with their consumption [5].…”
Section: Introductionmentioning
confidence: 99%